Deteksi dan Identifikasi Virus pada Umbi Bawang Merah - Arif Kurniawan; Gede Suastika (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2013)
Shallot is an important horticultural crop in Indonesia. One of it’s production constraint is viral disease. Dispersal of viruses on shallots may occurre through shallots bulb trading. However, there is not much information regarding viruses infecting shallot bulbs. Laboratory study was conducted to detect and identify viruses associated with shallot. Random sampling was done for several varieties of shallots (Jawa, Biru, Nganjuk, and Brebes varieties) collected from Bantul Districs. Virus detection and identification was based on RT-PCR using specific primer of OYDV, SYSV, SLV, and ShVX followed by sequencing of the nucleotides. RT-PCR was only successfully amplified Shallot yellow stripe virus (SYSV) with size 749 bp, while other viruses were not detected. Disease incidence of SYSV on Java and Brebes varieties were 60% and 53.3% respectively. Nucleotide sequences of SYSV CP gene showed the highest homology to SYSV from China and South Korea.Key words: RT-PCR, sequencing nucleotides, Shallot yellow stripe virus